2012
DOI: 10.1128/jvi.00695-12
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Roles for Extracellular Signal-Regulated Kinase 1 (ERK1) and ERK2 in the Structure and Production of a Primate Gammaherpesvirus

Abstract: During their progression from intranuclear capsids to mature trilaminar virions, herpesviruses incorporate an extensive array of viral as well as a smaller subset of cellular proteins. Our laboratory previously reported that rhesus monkey rhadinovirus (RRV), a close homolog of the human pathogen Kaposi's sarcoma-associated herpesvirus (KSHV), is comprised of at least 33 different virally encoded proteins. In the current study, we found that RRV infection activated the extracellular signal-regulated kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 81 publications
2
23
0
Order By: Relevance
“…Although this small region is conserved among ␥2 herpesviruses, ORF45 homologues seem to differ in their abilities to activate RSK and ERK (E. Kuang and F. Zhu, unpublished data), suggesting additional regions are involved. Recent studies by other groups have confirmed critical roles of the ERK pathway in MHV-68 and RRV lytic infection cycles that are at least partially dependent on ORF45 (43)(44)(45). More studies are needed to elucidate the molecular mechanisms by which ORF45 causes persistent activation of RSK and ERK.…”
Section: Discussionmentioning
confidence: 99%
“…Although this small region is conserved among ␥2 herpesviruses, ORF45 homologues seem to differ in their abilities to activate RSK and ERK (E. Kuang and F. Zhu, unpublished data), suggesting additional regions are involved. Recent studies by other groups have confirmed critical roles of the ERK pathway in MHV-68 and RRV lytic infection cycles that are at least partially dependent on ORF45 (43)(44)(45). More studies are needed to elucidate the molecular mechanisms by which ORF45 causes persistent activation of RSK and ERK.…”
Section: Discussionmentioning
confidence: 99%
“…Following purification and cleavage of GST, the proteins were used by the University of Virginia Lymphocyte Culture Center to produce mouse monoclonal antibodies to ORF52 and ORF65/SCIP. Rabbit polyclonal anti-RRV ORF45 was generated by Open Biosystems, Inc. (28). Mouse monoclonal anti-RRV major capsid protein (MCP) and anti-glycoprotein B (gB) were kindly provided by Scott Wong at Oregon Health and Science University.…”
Section: Methodsmentioning
confidence: 99%
“…Though the process of tegumentation remains poorly defined, previous studies have found both cellular and viral proteins within the layer (22)(23)(24)(25)(26)(27). This gives rise to a proteomic tegument profile that is distinct for each viral species and possibly even within the same species grown in different cell types or under different conditions (28). Until recently, structural data for the tegument were limited to images from electron microscopy (EM) that suggested that the layer was comprised of an amorphous collection of proteins; however, more recent studies with human cytomegalovirus (HCMV) (29), herpes simplex virus 1 (HSV-1) (30,31), murine gammaherpesvirus 68 (MHV-68) (32), RRV (33), and KSHV (34) indicate the presence of ordered tegument structures (30).…”
mentioning
confidence: 99%
“…Perturbation responses can diverge with the addition of one regulatory edge, which we demonstrate by using simple and detailed kinetic models complemented with experiments. In the MAPK literature, there are reports of surprising discrepancies between inhibitor and knockdown responses (Beliveau et al, 2010; Woodson and Kedes, 2012). As with the other wiring motifs, we believe that these discrepancies could be reconciled with the strength of ERK –| Raf feedback, which varies depending on cellular context (Pratilas et al, 2009).…”
Section: Discussionmentioning
confidence: 99%